PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PERUSAHAAN MAKANAN DAN MINUMAN DI BEI - Candra Irawan (CV. ALIM'SPUBLISHING, 2023)
The purpose of this study was to determine the effect of cash turnover, accounts receivable turnover and inventory turnover on the profitability of food and beverages listed on the Indonesia Stock Exchange. The population in this study were 26 issuers listed on the stock market, especially food and beverages, while the research sampling technique used purposive sampling, so the research sample was 20 companies or issuers. The results of this study are cash turnover has a significant negative effect on profitability, accounts receivable turnover has a significant negative effect on profitability, and inventory turnover has no effect on profitability